2023
DOI: 10.1186/s12957-023-03182-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergency resection is an independent risk factor for decreased long-term overall survival in colorectal cancer: a matched-pair analysis

Katharina Esswein,
Marijana Ninkovic,
Elisabeth Gasser
et al.

Abstract: Background Colorectal cancer is one of the most common malignant neoplasms worldwide. Up to 30% of the patients present in an emergency setting despite an established screening program. Emergency colorectal resection is associated with increased mortality and morbidity as well as worse oncological outcome. This study aims to analyze the impact on tumor recurrence and survival in patients with an emergency colorectal resection, independent of sex, age, and tumor stage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The LapEmerge trial has a unique setting of evaluating the oncological outcome of these patients, also taking into account the quality of the surgical specimen. Since emergency colon resections for oncologic patients are inevitable and the oncologic outcome is clearly inferior to elective surgery [ 44 ], this aspect of the trial is of the utmost importance. Overall, both of these trials, which are complementary, will provide novel information on both the short- and long-term effects and safety of laparoscopy in emergency colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The LapEmerge trial has a unique setting of evaluating the oncological outcome of these patients, also taking into account the quality of the surgical specimen. Since emergency colon resections for oncologic patients are inevitable and the oncologic outcome is clearly inferior to elective surgery [ 44 ], this aspect of the trial is of the utmost importance. Overall, both of these trials, which are complementary, will provide novel information on both the short- and long-term effects and safety of laparoscopy in emergency colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Austria including 59 patients (4.5%) who underwent emergency colectomy for colorectal carcinoma among 1297 patients treated with elective colectomy for colorectal carcinoma found that emergency resection reduced 5-year overall survival (35.6% vs 64.4%) and disease-free survival (54.2% vs 75.4%) and increased 1-year recurrence (47.5% vs 25.4%) rates. The 5-year overall survival rate for elective cases was higher in laparoscopic than open colectomy (71.4% vs 62.2%)[ 4 ]. Right-sided obstruction, despite more primary resections and anastomoses, is related to a worse prognosis than left-sided obstruction[ 45 ].…”
Section: Surgerymentioning
confidence: 99%
“…It is the third most common carcinoma, after lung, and breast or prostate carcinoma and the second leading cause of cancer-related deaths, after lung carcinoma, in the United States and Western Europe, causing more than 50000 deaths annually in the United States[ 1 - 3 ]. Early detection and proper management improves survival and avoids complications (mainly obstruction, perforation, bleeding, and fistula)[ 4 - 8 ].…”
Section: Introductionmentioning
confidence: 99%